The relationship between performance appraisal and demographic towards job satisfaction among employees in Johor Corporation / Norazilah Ab. Jabar - Ab. Jabar, Norazilah (Faculty of Business and Management, 2010)
The purpose of this paper is to examine the role of performance appraisals on human resource management outcome, which is job satisfaction. PA process is a complex and sophisticated subject. Organizations around the world are facing similar challenges which are the difficulty to conduct this process. It is not easy to evaluate employees’ performance. This research has tended to focus on the relationship between features of a PA process and HR outcome (job satisfaction). Organizations need to acknowledge the importance of the overall PA experience when evaluating its consequences for HRM outcome. This study has been conducted within JCorp and it involved 97 respondent’s indifferent department. Results of this study showed that all PA features have significant relationship with employees’ job satisfaction in JCorp. Recommendations for future research are also have been discussed.